Hospitality managers in turbulent times: the COVID-19 crisis. Issue 4 (12th February 2021) - Giousmpasoglou, Charalampos; Marinakou, Evangelia; Zopiatis, Anastasios
Abstract : Purpose: This study aims to explore the role General Managers (GMs) play in mitigating the effects of the unprecedented COVID-19 pandemic. Design/methodology/approach: Qualitative structured interviews conducted online with 50 hospitality GMs from 45 countries are used to explore the impact of the pandemic on the industry's operational norms and the role of managers in both managing the crisis and planning contingencies for recovery. Findings: The findings enhance the conceptual capital in this emerging field and provide insights on how GMs behave during crises. Four related sub-themes emerged from the data analysis, namely, contingency planning and crisis management, resilience and impact on GM roles, the impact on hotels' key functional areas and some GMs' suggestions for the future of luxury hospitality. Research limitations/implications: This study generates empirical data that inform contemporary debates about crisis management and resilience in hospitality organizations at a micro-level operational perspective. Practical implications: Findings suggest that, in times of uncertainty and crisis, luxury hotel GMs are vital in coping with changes and leading their organizations to recovery. GMs' resilience and renewed role and abilities enable them to adapt rapidly to external changes on their business environment. Originality/value: This study is unique in terms of scale and depth, as it provides useful insights regarding the GM's role during an unprecedented crisis such as COVID-19.